Imidoaryl biphenol based new fluorinated sulfonated poly(arylene ether sulfone) copolymers and their proton exchange membrane properties - Mohanty, Aruna Kumar; Banerjee, Susanta; Komber, Hartmut; Voit, Brigitte (Solid State Ionics, 2014)
A series of new partially fluorinated sulfonated poly(arylene ether sulfone) (IBQSH-XX) copolymers based on imidoaryl biphenol (IB) such as 3,8-bis(4-hydroxyphenyl)-N-phenyl-1,2-naphthalimide were synthesized by potassium carbonate mediated aromatic nucleophilic substitution reaction. The content of the sulfonated comonomer 3,3′-disodiumsulfonyl-4,4′- dichlorodiphenylsulfone was varied to obtain a degree of sulfonation from 0.2 to 0.6. The copolymers showed number average molar masses as high as 60 kDa and good solubility in various aprotic polar solvents. The copolymer structures were confirmed by FTIR and NMR spectroscopy. The IB moiety in the copolymers contributed decisively for very high thermal stability, oxidative stability and mechanical properties. Transmission electron microscopy (TEM) showed good phase separated morphology with ionic cluster size in the range of 3-60 nm for the copolymer membranes. The copolymer membranes showed good dimensional stability with very low water uptake and swelling ratios due to the rigid aromatic backbone moieties. Ion exchange capacity (IECW) of the copolymer films was calculated from the monomer composition obtained by 1H NMR spectroscopy and was further determined by titration methods. The proton conductivities of the copolymer membranes increase with degree of sulfonation and temperature maximum up to 49 mS/cm at 80 C. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Fluorinated co-poly(arylene ether sulfone)s; Proton conductivity; Structure-property relationship